KONSEP APLIKATIF FIQH MUAMALAH TERHADAP PELAKSANAAN UPAH DI DESA PRAMBATAN KECAMATAN ABAB KABUPATEN PALI - QADARIAH BARKAH; PENY CAHAYA AZWARI; ZUUL FITRIANI UMARI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study explores the model of wage implementation and review of Muqalah Fiqh on the implementation of wages in Prambat Village, Abab District, Pali Regency from January 2017 to February 2017. This type of data is descriptive qualitative research. Data sources are primary and secondary. Data collection through Observation and Interview to respondents who conduct wage implementation and people employed in. Participants were interviewed by garden owners, who held wages, Village Heads, workers in wages of 3 people. Processing and analyzing data with qualitative descriptive analysis. The results showed that the implementation of daily wages in the Prambat village did not conflict with Islamic law but there was a lack of clarity regarding the amount of wages and the time to pay wages. Parties who feel disadvantaged are workers. Implementation of daily wages in the form of ijarah and allowed in muamalah fiqh but there is one condition or pillar that is not fulfilled such as wages in implementing daily wages that are unclear how much and the time of payment and in muamalah must be clear, both wage amount and payment time. The solution, the qabul agreement between the two and the agreement on what matters relating to the transaction will be carried out. The results of observations and interviews indicate that the payment of wages has not been determined by the owner of the garden, both from the price of payment and the time of payment the agreement is unclear.